Technostress in Spanish University Students: Validation of a Measurement Scale - Penado Abilleira, María; Rodicio-García, María Luisa; Ríos-de-Deus, María Paula; Mosquera-González, María José (Frontiers in Psychology, 2020)
The increasingly widespread use of technology has led to the emergence of phenomena harmful to users such as technostress. Although technostress has already been studied in other contexts, it is still pending study in a university education environment, where the use of information and communication technologies is increasingly widespread. Thus, the objective of this study was to adapt a technostress questionnaire for Spanish university students based on an instrument that had been designed in a Chinese university teaching population. A total of 1.744 Spanish university students from face-to-face and online universities completed the adapted Spanish technostress scale. Factorial analyses suggested the elimination of two items from the original scale and a model made up of five factors that fit, as in the original scale, within the person-environment misfit theory. The reduced scale also showed good internal consistency for all the items and the five resulting factors. These results support the psychometric properties of the reduced technostress scale in university students, and their validity when offering a complete view of the phenomenon in Spain.